COMPARISON OF THREE ANTIBIOTICS REGIMENS IN THE TREATMENT OF ACUTE PYOGENIC MENINGITIS: Comparison of three Antibiotics Regimens - Waheed, Akhtar; Gardezi, Syed Anees Ahmed (Pakistan Armed Forces Medical Journal, 2008)
Object: Aim of this study is to compare various antibiotics in setting of acute pyogenic meningitis. Design: A quasi-experimental study. Place and Duration of Study: CMH Kohat from Dec 1999 to March 2002. Patients and Methods: Study was conducted in department of medicine Combined Military Hospital Kohat from Dec 1999 to March 2002. A total of sixty patients with provisional diagnosis of acute pyogenic meningitis between 13 – 50 years age belonging to heterogenous group of population mainly recruits from various military training centers were included in the study. Ten patients were excluded from study because of negative cerebro spinal fluid findings. These patients were started on group A antibiotics (Ceftriaxone, Ampicillin plus Chloramphenicol), group B (Ampicillin plus Chloramphenicol) and group C (Ceftrixone) at random. Result: The analysis of results of treatment with three different treatment regimens was done by noting complete recovery, complications and death. Twenty patients who were given group A regimen showed 90% complete recovery, one patient developed fulminant menigococcemia recovered fully and another patient developed deafness with gradual recovery (10% complications). Amongst fifteen patients in group B regimen 87% patients showed complete recovery, one patient developed seizure finally controlled, another patient developed hydrocephalus and was referred for shunt procedures (13% complications). Fifteen patients who were started group C regimen 93.33% patients fully recovered and one patient developed fulminant meningococcemia completely recovered but developed gangrene of toes for which amputation was done at a later stage (7% complications). The results of three treatment regimens were compared by using chi square test and were almost comparable (p-value > 0.05). Conclusion: In the empirical treatment of acute pyogenic meningitis, ceftriaxone alone cheap, safe and is as effective as combination of ceftriaxone plus ampicillin plus chloromphenicol or combination ampicillin plus chloromphenicol.